2013
DOI: 10.1021/jz400782j
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Behavior of Water Molecules Confined to Nanocavities in Gemstones

Abstract: When water is confined to nanocavities, its quantum mechanical behavior can be revealed by terahertz spectroscopy. We place H2O molecules in the nanopores of a beryl crystal lattice and observe a rich and highly anisotropic set of absorption lines in the terahertz spectral range. Two bands can be identified, which originate from translational and librational motions of the water molecule isolated within the cage; they correspond to the analogous broad bands in liquid water and ice. In the present case of well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 30 publications
4
37
0
2
Order By: Relevance
“…While optical spectroscopic studies of synthetic beryl recently also proposed [14][15][16] that the water undergoes quantum tunneling, these data were subjected to complex treatment to extract energies and intensities of the excitations, and the reported transitions at 1.33 and 3.21 meV are inconsistent with the INS data, which are sensitive primarily to the motion of individual hydrogen atoms.…”
Section: Q⊥cmentioning
confidence: 99%
See 1 more Smart Citation
“…While optical spectroscopic studies of synthetic beryl recently also proposed [14][15][16] that the water undergoes quantum tunneling, these data were subjected to complex treatment to extract energies and intensities of the excitations, and the reported transitions at 1.33 and 3.21 meV are inconsistent with the INS data, which are sensitive primarily to the motion of individual hydrogen atoms.…”
Section: Q⊥cmentioning
confidence: 99%
“…Confined water can be almost free [11], without hydrogen bonds (HB), and display significant quantum behavior. Inelastic neutron scattering (INS) studies have demonstrated that in fullerenes such water exhibits quantum transitions between the para-and ortho-states [12,13], and it has been suggested that quantum tunneling of water explains the fine structure of the optical spectra of beryl [14][15]. INS provides a unique method to study the vibrational and quantum tunneling dynamics of hydrogencontaining materials because of the anomalously large incoherent neutron scattering crosssection of protium (H-1).…”
mentioning
confidence: 99%
“…Quantum effects have been considered to shed light on this molecular jumble. [8][9][10] Recently, quantum tunneling dynamics have been reported for water molecules confined in nanocavities of beryl crystals 11,12 and in gasphase clusters like (H2O)6. 13 The chemical shift anisotropy (CSA) of protons in water molecules is of particular interest since it has the potential of lifting the magnetic equivalence of the two protons.…”
Section: Introductionmentioning
confidence: 99%
“…Одиночные молекулы воды в высокосимметричном кристаллическом окружении представляют собой модельную систему для изучения свойств воды в " конфайнменте". Недавно свой-ства воды в берилле были исследованы нами методами диэлектрической терагерцeвой спектроскопии [10,11]. B частности, было показано, что пространственно-структурированное расположение воды в каналах берил-ла приводит к виртуальному сегнетоэлектричеству [12].…”
Section: субмиллиметровые спектры эпр иона Feunclassified
“…В данном случае имели место ограничения, связанные с наличием структурной воды в каналах берилла. Ранее [10,11] вследствие нарастания поглощения, связанного с водой в каналах, уменьшалась микроволновая мощность, про-ходящая через образец. Совокупность этих факторов привела к ограниченному диапазону углов при изме-рении угловой зависимости спектров.…”
Section: рис 2 частотно-полевая зависимость резонансных переходов иunclassified